(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The legal system of Vietnam in general, and criminal law in particular, has started to include provisions regarding legal responsibilities towards homosexual and transgender individuals. However, the specific regulations within the laws and the application methods in particular cases are highly complex. In modern society, the rights of homosexual and transgender individuals are increasingly recognized and given more attention. However, similar to some other areas, the rights of homosexual and transgender individuals in the criminal field are still a neglected issue. Therefore, for the first time, the Criminal Code of Vietnam in 2015 introduced the provision of ’other sexual relations’ to protect the rights and determine the criminal responsibility of offenders towards homosexual and transgender individuals. This study focuses on clarifying the legal issues regarding homosexual and transgender individuals in criminal law and based on that, presents some proposals for improving the legal framework.